2002
DOI: 10.1063/1.1524697
|View full text |Cite
|
Sign up to set email alerts
|

Surface-mediated structural transformation in CdTe nanoparticles dispersed in SiO2 thin films

Abstract: Nanoassembly control and optical absorption in CdTe-ZnO nanocomposite thin films J. Appl. Phys. 111, 034305 (2012); 10.1063/1.3679081 Microstructure and optical characterization of CdTe quantum dots synthesized in a record minimum time

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…The short inelastic mean free path of the core level electrons makes XPS a surface sensitive technique since the information depth does not increase more than a few monolayers. We have gainfully used XPS to probe the core shell structure of other nanomaterials in the recent past [15][16][17]. In this work denconvolution of the core-levels of different elements into gaussians components would also reveal the presence of different chemical states of Cd and Se along the depth of the CdSe nanocrystallites as observed in the present study.…”
Section: Introductionmentioning
confidence: 63%
“…The short inelastic mean free path of the core level electrons makes XPS a surface sensitive technique since the information depth does not increase more than a few monolayers. We have gainfully used XPS to probe the core shell structure of other nanomaterials in the recent past [15][16][17]. In this work denconvolution of the core-levels of different elements into gaussians components would also reveal the presence of different chemical states of Cd and Se along the depth of the CdSe nanocrystallites as observed in the present study.…”
Section: Introductionmentioning
confidence: 63%
“…This is also confirmed by TEM studies described in the next paragraph. [13]. Further, the lattice parameter 'a' was estimated from extrapolated NRF data.…”
Section: Methodsmentioning
confidence: 99%
“…In(OH) 3 has the face centered cubic structure with a lattice constant of 7.974 A and In 2 O 3 has a bixbyite type cubic structure with 10.123 A lattice constant. 18) In another study on CdTe nanoparticles dispersed in SiO 2 films, it has been observed that the presence of a crystalline CdTeO 3 layer around CdTe nanoparticles results in a large number of defects in CdTe structure 19) At higher sintering temperatures, In 2 O 3 structure becomes defect free and improves because of the removal of In(OH) 3 layer. The linear variation of the NRF vs d=d plots for samples annealed at temperatures higher than 350 C confirms this.…”
Section: Resultsmentioning
confidence: 99%